(untitled) (Research, Society and Development, 2021)
This study aimed to relate the smallest set of variables that compose the quality of soybean seeds lot under study, as well as to evaluate the influence of four industrial seed treatments and their respective slurry volumes on the physiological potential. The experiment was carried out in a completely randomized block design with 4 replicates and 24 treatments. The chemical treatments were: control (T1), micronutrient + polymer + drying powder (T2), bioregulator + polymer + drying powder (T3) and micronutrient + bioregulator + polymer + drying powder (T4). The seeds were stored for periods of 0, 15, 30, 45, 60 and 90 days and were subsequently evaluated for their physiological potential. In each storage period, the variable germination, first count, accelerated aging, emergence speed index, final emergence in the sand substrate, aerial part length, root length and total seedling length were evaluated. The main components of the standard germination test and first count were the ones that most contributed to explaining the variability of the original data. Increasing the volume of the slurry in the industrial seed treatment reduces the physiological quality of soybean seeds during storage.